2010
DOI: 10.1103/physrevlett.105.085504
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rhenium Nitrides

Abstract: We report the synthesis, structure, and properties of novel bulk rhenium nitrides, hexagonal Re2N, and Re3N. Both phases have very high bulk moduli of >400 GPa, similar to the most incompressible binary transition-metal (TM) carbides and nitrides found to date. However, in contrast to other incompressible TM carbides and nitrides, Re3N is better placed for potential technological applications, as it can be formed at relatively moderate pressures (13-16 GPa) and temperatures (1600-2400 K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
144
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 27 publications
21
144
1
Order By: Relevance
“…Since the synthesis of Re 3 N in 2010, 71 many experimental and computational studies have targeted the higher-nitrogen rhenium nitrides. 72 We predict a broad collection of nitrogenrich rhenium nitrides with compositions ReN, Re 3 N 4 , Re 3 N 5 , and ReN 2 that are all within 350 meV/atom above the hull and can be stabilized under Δμ N 2 up to +0.5 eV/N.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Since the synthesis of Re 3 N in 2010, 71 many experimental and computational studies have targeted the higher-nitrogen rhenium nitrides. 72 We predict a broad collection of nitrogenrich rhenium nitrides with compositions ReN, Re 3 N 4 , Re 3 N 5 , and ReN 2 that are all within 350 meV/atom above the hull and can be stabilized under Δμ N 2 up to +0.5 eV/N.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…In contrast, interstitial bimetallic nitrides can be prepared in large amounts at ambient pressure, 3 having them (e.g. Ni 2 Mo 3 N, Co 3 Mo 3 N, and Fe 3 Mo 3 N) similar mechanical properties to many ultra-hard compounds. 4 In particular, their compressibility is smaller than that of cubic Si 3 N 4 and comparable to that of cubic BN.…”
mentioning
confidence: 99%
“…1 In particular, transition metal nitrides and carbides have attracted special attention. 2 These refractory materials have numerous industrial applications and a promising future, on top of being of great interest to the scientific community. Many incompressible nitrides have been recently discovered combining the application of high-pressure (HP) and hightemperature.…”
mentioning
confidence: 99%
“…Rhenium diboride was believed to be intrinsically superhard [5], but its load invariant hardness is also less than 30 GPa because of electronic and structural instabilities of 5d electrons under finite shear strain [11]. Rhenium nitrides, recently synthesized by Friedrich et al [12] under high pressure and temperature, have found much interest because of their large bulk modulus of about 400 GPa, which is higher than that of ReB 2 of 334-371 GPa [5,13]. However, our recent first principles study showed that a combination of thermodynamic instability, relatively low shear moduli and strengths, and relatively soft polar Re-N bonds inherently limits their hardness [14].…”
mentioning
confidence: 99%